Child and Adolescent Psychodynamic Therapy: Using Q-Methodology in Process Research. Issue 1 (31st December 2022) - Goodman, Geoff
ABSTRACT: Psychotherapy for children and adolescents has been shown to be generally effective in treating a wide variety of psychological problems. In spite of this success, the field has been slow to identify the key therapeutic processes responsible for changes in psychiatric symptoms, emotional well-being, social relationships, and school functioning observed across theoretically different treatment models. The child and adolescent psychodynamic psychotherapy literature lags far behind the adult literature in assessing the change processes associated with the successful treatment of children and adolescents. This article reviews the rapidly growing literature engaged in the pursuit of articulating the change processes associated with successful treatment outcomes for children and adolescents. Two classes of change processes are reviewed: interaction structures (i.e., patterns of reciprocal therapist-patient interaction) and adherence to "brand-name" treatment models (e.g., child psychodynamic therapy). Researchers have used children's psychiatric diagnoses most commonly as moderators of significant process-outcome associations. This article will explore the contributions of the Child Psychotherapy Q-Set (CPQ) and Adolescent Psychotherapy Q-Set (APQ) to this field of study, while also reviewing some of the data analytic strategies used. Finally, an outline of the future directions of child and adolescent psychodynamic psychotherapy process research using the CPQ and APQ is suggested.